Cystic fibrosis presenting as kwashiorkor with florid skin rash. Issue 4 (October 1993) - Phillips, R J; Crock, C M; Dillon, M J; Clayton, P T; Curran, A; Harper, J I
Abstract : Two infants with a florid erythematous rash and generalised oedema, hypoalbuminaemia, and anaemia were found to have cystic fibrosis. This rare presentation is associated with false negative sweat tests, delays in diagnosis, and a considerable mortality. It is proposed that this presentation represents a manifestation of kwashiorkor secondary to malabsorption. The recognition that these infants have kwashiorkor provides some insight into the pathogenesis and management of their illness.